2007
DOI: 10.1096/fj.06-7254com
|View full text |Cite
|
Sign up to set email alerts
|

LAPSER1 is a putative cytokinetic tumor suppressor that shows the same centrosome and midbody subcellular localization pattern as p80 katanin

Abstract: Prostate cancer is one of the most common cancers in men, with more than 500,000 new worldwide cases reported annually, resulting in 200,000 deaths of mainly older men in developed countries. Existing treatments have not proved very effective in managing prostate cancer, and continuing efforts therefore are ongoing to explore novel targets and strategies for future therapies. LAPSER1 has been identified as a candidate tumor suppressor gene in prostate cancer, but its true functions remain unknown. We report he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 30 publications
(56 reference statements)
4
48
1
Order By: Relevance
“…We found that LAPSER1 seems to regulate the localization of ␤-catenin in neuronal cells by enhancing its nuclear export via a functional nuclear export sequence. Because a permanent increase of activated ␤-catenin within the nucleus is known to inhibit cell differentiation and apoptosis causing cancer in several tissues (52), these findings support the proposed function of LAPSER1 as a putative tumor suppressor gene (12,17) also in neurons. Because the elevated expression of TcfE2a was significantly prolonged in LAPSER1-depleted neurons, first evidence was provided that the regulated nuclear export of ␤-catenin is one mechanism to terminate ␤-catenindependent gene transcription.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We found that LAPSER1 seems to regulate the localization of ␤-catenin in neuronal cells by enhancing its nuclear export via a functional nuclear export sequence. Because a permanent increase of activated ␤-catenin within the nucleus is known to inhibit cell differentiation and apoptosis causing cancer in several tissues (52), these findings support the proposed function of LAPSER1 as a putative tumor suppressor gene (12,17) also in neurons. Because the elevated expression of TcfE2a was significantly prolonged in LAPSER1-depleted neurons, first evidence was provided that the regulated nuclear export of ␤-catenin is one mechanism to terminate ␤-catenindependent gene transcription.…”
Section: Discussionsupporting
confidence: 55%
“…Fezzins are a family of PSD proteins (LAPSER1/LZTS2 (12), ProSAPiP1/LZTS3 (13), PSD-Zip70/LZTS1 (14,15), and N4BP3 (16)) that are able to build homo-and heterooligomers and are defined by a conserved Fez1 domain with hitherto unknown function. LAPSER1 has been initially characterized as a putative tumor suppressor gene according to its ability to inhibit cell growth when overexpressed (12) and has been reported to be involved in cytokinesis colocalizing with centrosomes and interacting with ␥-tubulin and p80 katanin (17). Thyssen et al (18) showed that LAPSER1 containing various domains of a potential transcription factor can indeed enter the nuclear compartment and interacts with ␤-catenin.…”
mentioning
confidence: 99%
“…The underlying central spindle microtubules are compacted into a tight midbody structure, which is then disassembled during abscission of the daughter cells through a process that appears to involve microtubule severing. Both katanin and spastin localize to the midbody through interactions with LAPSER1 (for 'rich in leucine, alanine, proline, serine, glutamate and arginine 1'; also known as LZTS2) and components of the endosomal sorting complex required for transport (ESCRT) complex, respectively, and their inhibition delays midbody disassembly and abscission in some cell types (Errico et al, 2004;Guizetti et al, 2011;Schiel and Prekeris, 2010;Sharma et al, 2007;Sudo and Maru, 2007). However, it is currently unclear whether these proteins actually directly sever and/or disassemble midbody microtubules and two very recent studies on the role of spastin in cytokinesis have come to opposite conclusions as to whether this is so (Guizetti et al, 2011;Schiel and Prekeris, 2010).…”
Section: Severing Enzymes In Cytokinesismentioning
confidence: 99%
“…The effect of LZTS2 on ␤-catenin was observed during human adipose tissue differentiation and synaptic cross-talk in neural tissue (7,8). In addition, LZTS2 has been shown to associate with p80 karatin and inhibit central spindle formation by abrogating microtubule transportation (9,10).…”
mentioning
confidence: 99%